Factors associated with increases over time in the quality of Active Support in supported accommodation services for people with intellectual disabilities: A multi-level model. (November 2019) - Bould, Emma; Bigby, Christine; Iacono, Teresa; Beadle-Brown, Julie
Abstract: Background: Disability support organisations have embraced Active Support, but it has proved difficult to embed in services. Aims: This study aimed to identify the factors associated with increases over time in the quality of Active Support. Method: Data were collected on the predicted variable of the quality of Active Support, and predictor variables of service user, staff and service characteristics, including practice leadership, and composition and size of services from 51 services in 8 organisations over 2–7 time points. Data were analysed using multi-level modelling. Results: There was significant linear change in Active Support scores (group mean centered at the organisational level) over time. Individuals with lower support needs received better Active Support and those with higher support needs experienced greater increases over time. Stronger practice leadership and more staff with training in Active Support were significant predictors of the quality of Active Support. Larger services with seven or more individuals and where there was a very heterogeneous mix of individuals were associated with lower quality of support. Conclusions: Ensuring strong practice leadership, and staff training in Active Support that emphasises the principle of adapting support to each individual's level of ability and preferences are key to delivering high levels of Active Support.